Anglers Perceptions About European Catfish Silurus glanis in a Newly Invaded Region - João Gago; Rui Rivaes; Diogo Ribeiro; Diogo Dias; Paul Castagné; Frédéric Santoul; Filipe Ribeiro (Diversity)
To avoid the spread and environmental impacts of the European catfish (Silurus glanis), which arrived in Portugal around 2006, it is fundamental to understand anglers’ behaviors and perceptions. To address this need, 339 Portuguese anglers were surveyed online and face-to-face and divided into two groups (catfish anglers, n = 115; and non-catfish anglers, n = 224). The majority of surveyed anglers were males (>95%) who consider that catfish is not beneficial to the development of angling (>62%) and acknowledge its negative impact on other fish species (>84%), mainly by predation (>89%). Catfish anglers perceive the species as more positive for angling and for other fish species. Principal Component Analysis showed that anglers’ behaviors are mainly driven by their awareness of the impacts of European catfish and by their angling experience. Regression modeling inferred the probabilities of two anglers’ behavior (targeting catfish and practice of catch and release) and one perception (catfish is beneficial to angling), which are considered promoters of catfish invasion, and detected strong correlations among these three variables. Therefore, it is strongly advised to implement an educational and law enforcement program to stop illegal practices that promote the dissemination of invasive fish species like European catfish.